Microbiology of diabetic foot infections in three district hospital in Malaysia and comparison with South East Asian Countries - Kow, Ren Yi; Low, Chooi Leng; Jaya Kumar, Ruben; Mustapha@Zakaria, Zaharul Azri; Mor Japar Khan, Ed Simor Khan (Malaysian Medical Association, 2019)
Introduction: Diabetic foot infection, a complication that is associated with lower-limb amputation, incurs a huge economic burden to the hospital and health care system of Malaysia. The bacteriological profile of pathogens in diabetic foot infections in Malaysia has been sparsely studied. We investigated the microbiology of diabetic foot infections in patients admitted to the district hospitals on the east coast of Malaysia. Methods: A retrospective analysis was conducted in three district hospitals (Hospital Kuala Lipis, Hospital Bentong and Hospital Raub) in Malaysia from 1st of January 2016 to 31st December 2016. The clinical specimens were cultured using Clinical and Laboratory Standards Institute (CLSI) guidelines. Antibiotic sensitivity testing to different antibiotics was carried out using the disc diffusion method. Result: A total of 188 pathogens were isolated from 173 patients, with an average of 1.09 pathogens per lesion. Majority of the pathogens isolated were gram negative pathogens (73.4%). The most commonly isolated pathogens were Staphylococcus aureus (17.5%). This was followed by Klebsiella spp. (17%), Pseudomonas spp. (15.4%) and Proteus spp. (13.8%). Gram positive pathogens were sensitive to most of the antibiotics tested except penicillin and fusidic acid. Gram negative pathogens were sensitive to all antibiotics tested except ampicillin and amoxicillin/clavulanic acid. Amikacin provide coverage for all gram negative pathogens in DFI. Conclusion: For the management of patient with infection in diabetic foot, the choice of antibiotic therapy depends on the sensitivity of the pathogens, the severity of the infection, the patient’s allergies history, toxicity and excretion of the antibiotics.